Cold, cholinergic and aquagenic urticaria in children: presentation of three cases and review of the literature - Arıkan-Ayyıldız, Zeynep; Işık, Sakine; Cağlayan-Sözmen, Sule; Karaman, Ozkan; Uzuner, Nevin (The Turkish Journal of Pediatrics, 2013)
Urticaria can be induced with a wide variety of environmental stimuli, such as cold, pressure, vibration, sunlight, exercise, temperature changes, heat, and water. Urticaria caused by physical factors has been reported as the cause of 6-17% of the chronic urticaria in children. We present three cases here - cholinergic, cold and aquagenic urticaria - in which the diagnosis was proven with exercise, ice-cube and water provocation tests, respectively.